The relationship between cultural capital and the students' perception of feedback across 75 countries: Evidence from PISA 2018. (2021) - Eryilmaz, Nurullah; Sandoval-Hernández, Andrés
Highlights: The objectified and embodied components of cultural capital have a positive effect on students' perception of feedback across all analysed countries. Institutionalised cultural capital did not show a significant effect on students' perception of feedback in most countries. Boys perceived receiving considerably more feedback than girls across all the analysed countries. There is a need for in-depth qualitative examinations to unveil the mechanisms underlying the patterns that we describe here. Abstract: This paper employs Pierre Bourdieu's cultural capital theory to examine the extent to which students' cultural capital is related to teacher-student interaction in the context of feedback. The study uses PISA (2018) data to implement multilevel modelling for each participating country. The findings show that objectified and embodied components of cultural capital have a positive and statistically significant effect on students' perception of feedback across all countries. Institutionalised cultural capital, however, has no significant effect in most countries. Furthermore, the findings show that boys perceived receiving considerably more feedback than girls. Recommendations for future studies and implications for theory, practice and policy are discussed.